2021
DOI: 10.1016/j.jtcme.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of onopordia, a novel isolated compound from Onopordon acanthium, on pentylenetetrazole-induced seizures in mice: Possible involvement of nitric oxide pathway

Abstract: Epilepsy is identified as a brain disorder and characterized by unpredictable disruption of normal brain function. Due to adverse side effect associated with antiepileptic drugs and also resistance profile, improvement of antiepileptic medications with more beneficial anticonvulsant activity is essential. Natural products have demonstrated their therapeutic properties such as anxiolytic, antidepressant and anticonvulsant activities and a source for identification of novel lead compounds. Therefore, the purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Administration of ketamine as an N-Methyl-D-aspartic acid receptor antagonist (0.5 mg/kg; ip) with onopordia did not change the anticonvulsant effect of onopordia. The results indicated that the antiepileptic effect of onopordia was attributed to NO/nNOS pathway on PTZ-induced seizure in mice [95].…”
Section: Onopordon Acanthiummentioning
confidence: 88%
“…Administration of ketamine as an N-Methyl-D-aspartic acid receptor antagonist (0.5 mg/kg; ip) with onopordia did not change the anticonvulsant effect of onopordia. The results indicated that the antiepileptic effect of onopordia was attributed to NO/nNOS pathway on PTZ-induced seizure in mice [95].…”
Section: Onopordon Acanthiummentioning
confidence: 88%
“…Administration of ketamine as a N-Methyl-D-aspartic acid receptor antagonist with onopordia did not change the anticonvulsant effect of onopordia. 33 Plasma is proof the biochemical parameters (AST, ALT, APT, bilirubin and cholesterol) and histopathological analysis. However, the mechanism of oxidative pressure in TAA hepatotoxicity is still not clear.…”
Section: Discussionmentioning
confidence: 99%